POTENSI USAHA TOURISM WEB SERVICE WWW.AYOHOLIDAY.COM KAISA GROUP SEMARANG - Ester Wulandari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Scientific study activities on tourism, mice, and marketing communications. The activities carried out are in the form of participating in discussions and assigned to attend seminars, aiming to enrich knowledge about tourism, mice and marketing communications. This activity is a practice to process vendor data that will collaborate with the office into one in the service provider partner file. Both transportation, accommodation, restaurants, logistics and human resources. Aims to collect data on cooperation partners so that the data is neat and can be searched at any time when needed